ANTESEDEN DARI MINAT PEMBELIAN PRODUK SHAMPO NATURAL DAN ORGANIK - Haro, Andrian (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
ANTESEDEN DARI MINAT PEMBELIAN PRODUK SHAMPO NATURAL DAN ORGANIKAndrian HaroFakultas Ekonomi Universitas Negeri Jakartae-mail: andrianharo@feunj.ac.idABSTRACTThe objective of this research is to examine the consumer purchase intention of natural and organic shampoo products based on the Theory of Planned Behavior (TPB). Specifically, this research considers that consumer values as antecedents of consumers’ attitude toward buying natural and organic shampoo products. A survey was conducted with many respondents from graduate students of Magister Management, Trisakti University, Jakarta, and structural equation modeling techniques was used to test the relationships among the variables. The results show that environmental consciousness and appearance consciousness have a positive effect on attitude. Meanwhile, health consciousness has no significant effect on consumers’ attitude. Moreover, the results showed that TPB predictors which consist of attitude and perceived behavioral control are significantly correlated with purchase intention for natural and organic shampoo products, but not with subjective norm. This research provides valuable insight into consumer purchase intention behavior regarding natural and organic shampoo products by examining the factors that influence consumers’ attitude toward buying natural and organic shampoo products and consumers’ purchase intentions for the products.Keywords: Consumer Behaviour, Theory of Planned Behavior, Attitude, PurchaseIntention, Personal Care